ANALISIS YURIDIS TERHADAP PERATURAN BERSAMA KETUA MARI, MENTERI HUKUM DAN HAM, JAKSA AGUNG DAN KAPOLRI TAHUN 2010 TERHADAP BATASAN WAKTU PELAKSANAAN EKSEKUSI TERPIDANA MATI BERDASARKAN UNDANG-UNDANG NO 35 TAHUN 2009 TENTANG NARKOTIKA - Jainah Ompu Zainab; Muharam Asih Novi (Universitas Bandar Lampung (UBL), 2022)
Drug abuse appears in the mass media, both in newspapers, magazines, television, radio and the internet. The problem of narcotics has now penetrated all elements of the nation, from children to adults, from the lower classes to officials, artists, even politicians and law enforcement are also not sterile from narcotics abuse. As stipulated in the attachment of Law no. 22 of 1997 concerning Junto Law no. 35 of 2009 concerning Narcotics, it is stated that importing, exporting, producing, using narcotics without strict control and supervision, and contrary to applicable laws and regulations is a crime because it is very detrimental and is a very big danger to human life, society, nation. , and the state and national resilience of Indonesia. Based on the existing background, the authors conducted a research entitled Normative Juridical Analysis of Joint Regulations of the Chairperson of MARI, Minister of Law and Human Rights, Attorney General and National Police Chief in 2010 Against the Time Limit for Execution of Death Convicts Based on Law No. 35 of 2009 concerning Narcotics. The enforcement of the death penalty in narcotics crimes based on L Friedman's system theory regarding law enforcement can be seen from the legal structure, where quality and good law enforcement officers such as the police, BNN will determine the success of the law enforcement process. Then the death penalty is also maintained based on reasons of public interest (public protection), but in its implementation it also pays attention to individual interests/protection.